The inventorying and mapping of landslide potential in Manado â Indonesia - Kumajas, Mithel (Universitas Muhammadiyah Surakarta, 2006)
Landslide constitutes a frequent problem occurs in Manado. It happens for many times from year to year and brings both material disadvantage and casualty. The way and hilly topography of Manado, unstabel geological condition, high rainfall, and the improper land use are assumed to be the trigger for the problem. The objective of this study is to inventory and map landslide potential area as well as to design the preventive plan. Mapping method employs spatial approach by using land unit as the analysis unit. The technique of analysis applies the assistance of GIS with its ArcView soft ware. The result of mapping shows that the level landslide potential from potential until very potential category in Manado is 1.815,72 Ha; potential is 1282,10 ha and very potential category is 533,62 ha. The faktors cause the landslide comprise of rocky declivity, high rainfall, and the condition of stone as well as the unstabel and porous soil. The existence of Cesar zone extends to the center of the city and the use of settlement land located in improper zone become the trigger that quicken the occurrence of landslide. The strategy implemented to manage the landslide potential area can be carried out through 1) law enforcement in relation to city lay out, 2) landslide prevention through civil and vegetative technique, 3) the improvement of social consciousness of the danger of landslide disaster and the attempt for social empowerment, and 4) the provision of the landslide potential danger map as the ground for policy making in the effort to manage the landslide disaster.